Review on sliding mode control and its application in electrohydraulic actuator system - Othman, Siti Marhainis (Asian Research Publishing Network (ARPN), 2015)
The purpose of this paper is to review the literatures related to the modeling of sliding mode control strategies of hydraulic actuator systems proposed by various researchers in order to design a high performance nonlinear controller in the presence of uncertainties. Sliding mode controller (SMC) is one of the nonlinear robust controllers which can be used in nonlinear dynamic systems with uncertainty. Before the main discussion, background information related to the hydraulic actuators will be presented. This review is concluded with a short summary and conclusion of hydraulic actuators.